Can new doctors be prepared for practice? A review. (June 2014) - Cameron, Alexander; Millar, James; Szmidt, Natasha; Hanlon, Katie; Cleland, Jennifer
Summary Background The transition from medical student to junior doctor is an important period of change. Research shows junior doctors often experience high levels of stress, and consequently burnout. Understanding how to prepare for the transition may allow individuals who are likely to struggle to be identified and assisted. The aim of this paper is to systematically review the literature on preparedness for practice in newly qualified junior doctors. Methods This was a systematic review of literature concerning the transition from student to junior doctor, published in the last 10 years, and that measured or explored one or more factors affecting preparedness. Results Nine papers were included in this review. These varied in design and methodological quality. Most used survey methodology (n = 7). Six found knowledge and skills, particularly deficiencies in prescribing and practical procedures, relevant in terms of preparedness. Five looked at personal traits, with high levels of neuroticism and low confidence deemed to be important. Medical school and workplace factors, including early clinical experience and shadowing, positively affected preparedness. A lack of senior support proved detrimental. The influence of demographics was inconclusive. Discussion The studies reviewed indicate that both personal and organisational factors are pertinent to managing the transition from student to junior doctor. Further prospective studies, both qualitative and quantitative, drawing on theories of change, are required to identify what precise factors would make a difference to this transition.